“DESA SEHAT BERDAYA” Inovasi Kesehatan & Ekonomi Lokal Berbasis Digital - Intan Yulia Lestari; Muhammad Iklil Fauzan Kohongia; Sriwandi Junaidi; Fathia Nur Mawaddah Uno; Dewi Anggraini A. Latoko; Ranisa Rahman; Anisa Canon (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
The